2013
DOI: 10.1093/icvts/ivt130
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events of pulmonary vascular stapling in thoracic surgery

Abstract: Generally, stapling of the pulmonary vasculatures in recent thoracic surgery has been safe. Furthermore, the knowledge of the possible risks of pulmonary vascular stapling may help to decrease the AEs of stapling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 9 publications
0
29
1
Order By: Relevance
“…Careful maneuvres and proficiency with all endoscopic instruments are essential. Yano et al [10] reported that the incidence of adverse events related to pulmonary vascular stapling in thoracic surgery was 0.27 % (9/3393). In terms of complications related to bleeding, they reported oozing (n = 2), laceration of the peripheral vasculature at compression (n = 2), and technical injury to the vasculature at insertion (n = 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Careful maneuvres and proficiency with all endoscopic instruments are essential. Yano et al [10] reported that the incidence of adverse events related to pulmonary vascular stapling in thoracic surgery was 0.27 % (9/3393). In terms of complications related to bleeding, they reported oozing (n = 2), laceration of the peripheral vasculature at compression (n = 2), and technical injury to the vasculature at insertion (n = 1).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the number of VATS operations for NSCLC is expected to increase. On the other hand, concerns have been raised about the safety of VATS, with reports of catastrophic intraoperative complications [8][9][10][11][12][13][14] including bleeding, transection of an entire artery, vein, or bronchus, contralateral nerve palsy, and bronchial injury. Notably, bleeding from the pulmonary arteries (PA) often requires changing the procedure…”
Section: Introductionmentioning
confidence: 99%
“…Sugarbaker and Mentzer 7 in 1992 published a technique for pulmonary artery stapling using two successive applications of the same stapler, and reloading without removing it, in order to address surgeons' reluctance to use vascular staplers of the TA-type in the pulmonary hilum. In contrast, Craig and Walker 8 in 1995 reported on 2 of 57 patients who underwent video-assisted thoracoscopic surgery lobectomy, who needed expeditious thoracotomy because of massive bleeding ensuing from vascular stapling Lobectomy complications list, n 40 (AF, n ¼ 10; PAL, n ¼ 11; chylothorax, n ¼ 2; atelectasis, n ¼ 6; pneumonia, n ¼ 3; stroke, n ¼ 1; ileus, n ¼ 2; DVT, n ¼ 2; PE, n ¼ 2; TIA, n ¼ 1) 10 having analyzed 3393 pulmonary artery and vein stapling applications on 4495 patients, with only a 0.27% adverse event rate, reported with reassurance that stapling of the pulmonary vasculature was safe. In our study we used only the conventional TA-30 vascular staplers for main pulmonary artery closures, during pneumonectomies, without any adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…In 2002 Asamura and coworkers published a series of 842 mechanical vascular divisions using endoscopic staplers, with a 0.1% incidence of stapling failure, and in 2013 Yano and coworkers reported on 3393 pulmonary artery and vein stapling applications, with an adverse event rate of only 0.27%, resulting in the cessation of the alarm. [7][8][9][10] In our hospital, during fiscal crisis there was a period of temporary shortage of stapling devices that drove us to manual suturing of bronchi and pulmonary hilum vessels during lobectomies and pneumonectomies, and in this study we present our experience during that time interval in comparison with a subsequent period when the supply of staplers was completely restored.…”
mentioning
confidence: 97%
“…Results from one survey indicate that 86% of minimally invasive surgeons have experienced an incident in which the linear stapler would not release (66%) or not fire (73%) after application, with 25% having to significantly alter the planned operative procedure because of the malfunction. 37 Yano and colleagues 38 reported a single institution experience of 9 adverse events out of 3393 stapler deployments (Fig. 1).…”
Section: Device Malfunctionmentioning
confidence: 99%